Composite current collector and preparation method and application thereof

By using composite liquid collectors in lithium-ion batteries, combining the structure of polymer film layer, lithium-philic compound nanoarray and metal layer, the lithium dendrites problem and insufficient mechanical strength of the current collector are solved, and the battery energy density and cycle life are improved.

CN119581569AActive Publication Date: 2025-03-07JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411785636.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, pure metal current collectors do not contribute to the increase in energy density, and there is a problem of lithium dendrite, which affects the safety performance and cycle stability of the battery.

Method used

Using composite fluid collections, including polymer film layers, lithium-philic compound nanoarrays and metal layers, electron conduction is achieved through the through-hole structure of the polymer film layer. The lithium-philic compound nanoarray promotes uniform deposition of lithium ions, and the metal layer enhances conductivity and stabilizes the presence of lithium-philic compound nanoarrays.

Benefits of technology

It improves the energy density and cycle life of the battery, reduces the probability of thermal runaway, enhances the mechanical flexibility and conductivity of the current collector, effectively regulates the directional deposition of lithium metal, and limits the growth of lithium dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581569A_ABST
    Figure CN119581569A_ABST
Patent Text Reader

Abstract

The invention provides a composite current collector and a preparation method and application thereof. The composite current collector comprises a polymer film layer which is provided with a through hole structure penetrating through the surfaces of the two sides; the lithium-loving compound nano arrays are distributed in non-porous areas on the surfaces of the two sides of the polymer film layer; and the metal layers are located in areas, where the lithium-loving compound nano array is not distributed, of the surfaces of the two sides of the polymer film layer. The composite current collector provided by the invention has the advantages of stable structure, tight combination of each structural layer, difficult falling and excellent mechanical flexibility, provides abundant deposition space for lithium ion deposition, enhances the conductivity of the current collector, improves the energy density and cycle life of the battery, and also reduces the occurrence probability of thermal runaway of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a composite current collector and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) have become the dominant technology for portable electronic devices, portable device power supplies, and energy storage due to their long service life and high energy efficiency. Over the past decade, the rapid development of various fields has put forward higher requirements for LIBs, especially higher energy density and better safety. In the traditional LIB structure, copper foil (ρ = 8.96 g / cm 3 ) or aluminum foil are usually used to support the active materials of the negative and positive electrodes, respectively. However, their combined mass accounts for more than 15% of the total weight of the LIB, but they do not contribute to the capacity, which greatly hinders the improvement of the overall energy density of the LIB. In order to solve the problem of lithium dendrites, scientific researchers have carried out a lot of research and made significant progress, which can be roughly summarized as follows:

[0003] (1) Constructing a three-dimensional conductive skeleton as a host material for metallic lithium can significantly improve the volume expansion problem during the circulation of metallic lithium. At the same time, the conductive skeleton can reduce the generation of "dead lithium" and thus improve the utilization rate of metallic lithium. For example, CN115000412A relates to a preparation method and application of a surface-modified carbon cloth 3D skeleton, and provides a preparation method of a surface-modified carbon cloth 3D skeleton, the preparation method comprising the following steps: 1) Preparation of hydrophilic carbon cloth: 2) Preparation of modified carbon cloth. However, a pure three-dimensional conductive skeleton structure may lead to uneven lithium metal deposition and the appearance of disordered dendrites, which may affect the safety performance and cycle stability of the battery;

[0004] (2) Use thinner metal current collectors, such as CN117026165A, which discloses a method for preparing ultra-thin current collectors using double-pulse ion beam technology, characterized in that the ultra-thin polymer is first baked and cleaned by a gas ion source, and then the plasma is deposited on the surface of the ultra-thin polymer through magnetic filtration deposition and magnetron sputtering to obtain the ultra-thin current collector. However, the thinning of metal foil also needs to fully consider the impact of mechanical properties, especially mechanical toughness, because the current collector needs good mechanical toughness to alleviate the stress caused by the volume change during the charge and discharge process of the active material. However, the production yield and mechanical strength of the thin foil brought about by the thinning of the foil are also limiting factors for ultra-thin metal current collectors;

[0005] (3) Promoting uniform deposition of lithium ions by constructing a lithium-philic coating, etc. For example, CN117059815A provides a lithium-philic supported current collector for an electrochemical cell for circulating lithium ions. The lithium-philic supported current collector includes a current collector substrate and a lithium-philic material. The lithium-philic material includes an element selected from indium, lead, bismuth, gold and a combination thereof. In some variations, the lithium-philic material is limited to a lithium-philic layer disposed on one or more surfaces of the current collector substrate or adjacent thereto. However, the lithium-philic coating is easily detached during the cycle, resulting in a decrease in the cycle performance.

[0006] Therefore, how to effectively solve the problem of lithium dendrites, ensure the mechanical strength of the current collector, and improve battery performance is a technical problem that needs to be solved urgently. Summary of the invention

[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide a composite current collector and a preparation method and application thereof. The composite current collector provided by the present invention has a stable structure, each structural layer is tightly combined, not easy to fall off, has excellent mechanical flexibility, provides abundant deposition space for lithium ion deposition, enhances the conductivity of the current collector, improves the energy density and cycle life of the battery, and also reduces the probability of thermal runaway of the battery.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a composite current collector, the composite current collector comprising:

[0010] A polymer film layer, wherein the polymer film layer has a through-hole structure penetrating through two side surfaces;

[0011] A lithium-philic compound nanoarray, wherein the lithium-philic compound nanoarray is distributed in the non-porous areas on both sides of the polymer membrane layer;

[0012] and a metal layer, wherein the metal layer is located in the area where the lithium-philic compound nanoarray is not distributed on the two side surfaces of the polymer film layer.

[0013] The composite current collector provided by the present invention has a composite structure of a polymer film layer, a lithium-philic compound nanoarray and a metal layer, which has excellent mechanical flexibility and reduces the probability of thermal runaway of the battery; the through-hole structure of the polymer film layer realizes electronic conduction on both sides; the lithium-philic compound nanoarray has excellent lithium-philic properties, which will cause lithium metal to be deposited along the surface of the lithium-philic compound nanoarray, and at the same time, the three-dimensional structure formed by the array constructed between the nanofibers can provide a very rich deposition space for lithium ion deposition, effectively slowing down the volume change of the negative electrode during the cycle; the specific distribution of the metal layer plays a role in improving the conductivity of the current collector, and the bonding force with the polymer film is stronger, so that the mutual reinforcement effect of the composite film is better played, and at the same time, the metal layer can also promote the stable existence of the lithium-philic compound nanoarray and prevent the lithium-philic compound nanoarray from falling off; and the composite current collector provided by the present invention has a low density and significantly improves the energy density of the battery.

[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] Preferably, the polymer in the polymer film layer includes at least one of polyimide, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate, polyethylene oxide or polyvinyl alcohol.

[0016] Preferably, the weight average molecular weight of the polymer in the polymer film layer is 10,000-50,000.

[0017] Preferably, the lithium-philic compound nanoarray comprises at least one of a copper oxide nanoarray, a titanium dioxide nanoarray or a nickel hydroxide nanoarray.

[0018] Preferably, the array height of the lithium-philic compound nanoarray is 2-5 μm.

[0019] Preferably, the lithium-philic compound nanoarray further comprises a modifier, wherein the modifier comprises a lithium-philic material, and the lithium-philic material comprises at least one of Au, Pt or Ag.

[0020] Preferably, the pore size of the through-hole structure is 5-20 μm.

[0021] Preferably, taking the thickness direction perpendicular to the polymer film layer as the horizontal direction, the hole center distance between adjacent through holes in the same horizontal direction is 500-5000 μm.

[0022] Preferably, the thickness T1 of the polymer film layer and the thickness T2 of the metal layer satisfy: 2 μm≤T1+T2≤9 μm, and / or, 1 / 2≤T1 / (T1+T2)≤5 / 7.

[0023] Preferably, the metal in the metal layer is also filled in the through hole.

[0024] In a second aspect, the present invention provides a method for preparing the composite current collector as described in the first aspect, the preparation method comprising the following steps:

[0025] The lithium-philic compound nanoarrays are grown on both sides of the polymer film layer containing the through-hole structure, and then the metal layers on both sides of the polymer surface are composited to obtain the composite current collector.

[0026] Preferably, the method for growing the lithium-philic compound nanoarray comprises:

[0027] The polymer film layer, chemical etching solution and lithium-philic compound precursor material are mixed and reacted to obtain a lithium-philic compound nanoarray.

[0028] Preferably, the lithium-philic compound nanoarray is modified, and the modification method includes: mixing a polymer film layer on which the lithium-philic compound nanoarray is grown with a lithium-philic material precursor solution, performing a modification reaction, and completing the modification of the lithium-philic compound nanoarray.

[0029] Preferably, the composite method of the metal layer comprises: preparing the metal layer on both side surfaces of the polymer film layer by vacuum evaporation to obtain the composite current collector.

[0030] In a third aspect, the present invention further provides a battery, comprising the composite current collector as described in the first aspect or the composite current collector prepared by the preparation method as described in the second aspect.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The composite current collector provided by the present invention cooperates with each other in structure and distribution, has excellent mechanical flexibility, is not easy to break, and even if it breaks, it cannot reach the standard of piercing the diaphragm, so that the risk caused by breakage can be better avoided and the thermal stability of the battery is improved; the through-hole structure of the polymer film layer realizes the electronic conduction on both sides, reduces the density of the composite current collector, and improves the energy density of the battery; the lithium-philic compound nanoarray has excellent lithium-philic properties, which will cause lithium metal to be deposited along the surface of the lithium-philic compound nanoarray, and at the same time, the three-dimensional structure formed by the array constructed between the nanofibers can provide a very rich deposition space for lithium ion deposition. It can effectively slow down the volume change of the negative electrode during the cycle and effectively regulate the directional deposition of lithium metal. The lithium-philic compound nanoarray as a carrier framework of lithium metal can not only reduce the local current density, but also limit the volume expansion of the negative electrode and the growth of lithium dendrites during the charge and discharge process, and also increase the contact points of the metal layer; the specific distribution of the metal layer plays a role in improving the conductivity of the current collector, and fills the area on the surface of the polymer film where the lithium-philic compound nanoarray is not distributed, making up for the distribution gap of the lithium-philic compound nanoarray, and having a stronger bonding force with the polymer film, and better playing the role of mutual reinforcement of the composite film, and at the same time can also promote the stable existence of the lithium-philic compound nanoarray and prevent the lithium-philic compound nanoarray from falling off. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the SEM image of Au@CuO@PPI provided in Example 1.

[0034] Figure 2 This is a SEM image of the composite current collector provided in Example 1.

[0035] Figure 3 It is a schematic diagram of the structure of the composite current collector provided in a specific embodiment of the present invention.

[0036] Among them, 1-polymer film layer, 2-through hole structure, 3-lithium-philic compound nanoarray, 4-metal layer. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in this application and any variations thereof are intended to cover non-exclusive inclusions.

[0039] In a specific embodiment, the present invention provides a composite current collector, the composite current collector comprising:

[0040] A polymer film layer, wherein the polymer film layer has a through-hole structure penetrating through two side surfaces;

[0041] A lithium-philic compound nanoarray, wherein the lithium-philic compound nanoarray is distributed in the non-porous areas on both sides of the polymer membrane layer;

[0042] and a metal layer, wherein the metal layer is located in the area where the lithium-philic compound nanoarray is not distributed on the two side surfaces of the polymer film layer.

[0043] The composite current collector provided by the present invention cooperates with each other in structure and distribution, has excellent mechanical flexibility, is not easy to break, and even if it breaks, it cannot reach the standard of piercing the diaphragm, so that the risk caused by the break can be better avoided and the thermal stability of the battery is improved; the through-hole structure of the polymer film layer realizes the electronic conduction on both sides, reduces the density of the composite current collector, and improves the energy density of the battery; the lithium-philic compound nanoarray has excellent lithium-philic properties, which will cause lithium metal to be deposited along the surface of the lithium-philic compound nanoarray, and at the same time, the three-dimensional structure formed by the array constructed between the nanofibers can provide a very rich deposition space for lithium ion deposition, which is The invention can effectively slow down the volume change of the negative electrode during the cycle and effectively regulate the directional deposition of lithium metal. The lithium-philic compound nanoarray as a carrier framework of lithium metal can not only reduce the local current density, but also limit the volume expansion of the negative electrode and the growth of lithium dendrites during the charge and discharge process, and increase the contact points of the metal layer. The specific distribution of the metal layer plays a role in improving the conductivity of the current collector, and fills the area on the surface of the polymer film layer where the lithium-philic compound nanoarray is not distributed, which makes up for the distribution gap of the lithium-philic compound nanoarray, has a stronger bonding force with the polymer film, and better plays the role of mutual reinforcement of the composite film. At the same time, it can also promote the stable existence of the lithium-philic compound nanoarray and prevent the lithium-philic compound nanoarray from falling off.

[0044] In the present invention, the distribution of the lithium-philic compound nanoarray and the metal layer in the polymer film layer cooperates with each other, that is, the metal layer makes up for the filling gaps of the nanoarray on the surface of the polymer film layer. If the lithium-philic compound nanoarray is not contained, uniform deposition of lithium ions cannot be achieved; and if the composite current collector does not contain a metal layer, it will lead to inconsistent interface resistance, resulting in the inability to uniformly deposit lithium ions; at the same time, if the polymer film layer is a non-through-hole structure, the surfaces on both sides of the polymer film layer (that is, the surfaces on both sides of the polymer film layer perpendicular to the thickness direction) cannot be conductive.

[0045] As a preferred technical solution in a specific implementation, the polymer in the polymer film layer includes at least one of polyimide, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate, polyethylene oxide or polyvinyl alcohol.

[0046] In the present invention, in addition to the limitation on the specific material types of the above-mentioned polymer film layer, conventional polymer types that can be used for current collectors and can be used to prepare through-hole structures are also applicable to the present invention.

[0047] As a preferred technical solution in a specific implementation, the weight average molecular weight of the polymer in the polymer film layer is 10,000 to 50,000, for example, 10,000, 15,000, 20,000, 25,000, 30,000, 35,000, 40,000, 45,000 or 50,000, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] In the present invention, the weight average molecular weight of the polymer in the polymer film layer is 10,000 to 50,000, which is more conducive to the growth of the lithium-philic compound nanoarray on the surface of the polymer film layer and the attachment of the metal layer.

[0049] As a preferred technical solution in a specific implementation, the lithium-philic compound nanoarray includes at least one of a copper oxide nanoarray, a titanium dioxide nanoarray or a nickel hydroxide nanoarray.

[0050] As a preferred technical solution in a specific embodiment, the array height of the lithium-philic compound nanoarray is 2 to 5 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In the present invention, the array height of the lithium-philic compound nanoarray is 2-5 μm, which can better achieve uniform deposition of lithium ions.

[0052] As a preferred technical solution in a specific embodiment, the lithium-philic compound nanoarray also includes a modifier, and the modifier includes a lithium-philic material, and the lithium-philic material includes at least one of Au, Pt or Ag.

[0053] In the present invention, further modification of the lithium-philic material in the lithium-philic compound nanoarray can not only modify the lithium-philic compound nanoarray and improve the conductivity, but also further induce the uniform deposition of lithium ions in the lithium-philic compound nanoarray, thereby promoting the long cycle performance of the battery, effectively reducing the accumulation of dead lithium on the negative electrode surface, and maintaining the lithium ion diffusion flux during the cycle.

[0054] As a preferred technical solution in a specific implementation, the pore size of the through-hole structure is 5 to 20 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] As a preferred technical solution in a specific implementation, with the horizontal direction perpendicular to the thickness direction of the polymer film layer, the center distance between adjacent through holes in the same horizontal direction is 500-5000μm, for example, 500μm, 1000μm, 1500μm, 2000μm, 2500μm, 3000μm, 3500μm, 4000μm, 4500μm or 5000μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In the present invention, by further adjusting the pore size of the through holes in the polymer film layer to 5-20 μm and the hole center distance to 500-5000 μm, the flexibility of the polymer film layer can be ensured, the electronic conductivity on both sides of the polymer film layer can be enhanced, and the effective distribution of the lithium-philic compound nanoarray and the metal layer can be achieved on the surface of the polymer film layer, thereby enhancing the bonding strength between the polymer film layer and the lithium-philic compound nanoarray and the metal layer.

[0057] As a preferred technical solution in a specific embodiment, the thickness T1 of the polymer film layer and the thickness T2 of the metal layer satisfy: 2μm≤T1+T2≤9μm, for example, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm or 9μm, etc., and / or, 1 / 2≤T1 / (T1+T2)≤5 / 7, for example, 1 / 2, 4 / 7 or 5 / 7, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] In the present invention, the relationship between the thickness T1 of the polymer film layer and the single-side thickness T2 of the metal layer is regulated, which is more conducive to reducing the weight of the current collector and increasing the energy density.

[0059] As a preferred technical solution in a specific implementation, the metal in the metal layer is also filled in the through hole.

[0060] In the present invention, the through holes of the polymer film layer are also filled with metal, which can better improve the conductivity of the composite current collector and enhance the combination of the metal layer, the lithium-philic compound nanoarray and the polymer film layer.

[0061] In another specific embodiment, the present invention provides a method for preparing the composite current collector as described in the above specific embodiment, the preparation method comprising the following steps:

[0062] The lithium-philic compound nanoarrays are grown on both sides of the polymer film layer containing the through-hole structure, and then the metal layers on both sides of the polymer surface are composited to obtain the composite current collector.

[0063] The preparation method provided by the present invention first realizes the growth of lithium-philic compound nanoarrays on the surface of the polymer film layer, and then performs composite filling of the metal layer, so as to obtain a composite current collector structure with a stable structure and a tighter combination; and the preparation process is simple to operate and does not require a complicated preparation process.

[0064] As another preferred technical solution in a specific embodiment, the growth method of the lithium-philic compound nanoarray includes:

[0065] The polymer film layer, chemical etching solution and lithium-philic compound precursor material are mixed and reacted to obtain a lithium-philic compound nanoarray.

[0066] In the present invention, the growth method of the lithium-philic compound nanoarray is to adaptively select the specific substance types of the chemical etching solution and the lithium-philic compound precursor material and adjust the ratio according to the specific substance types of the lithium-philic compound.

[0067] Optionally, the chemical etching solution includes a mixed solution of sodium hydroxide and ammonium persulfate, and the molar ratio of sodium hydroxide to ammonium persulfate is (0.1-2):1, for example, 0.1:1, 0.5:1, 1:1, 1.5:1 or 2:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] Optionally, the lithium-philic compound precursor material includes a copper salt (such as copper sulfate), a titanium salt (such as Li4Ti5O 12 ) or nickel salts (such as Ni(NO3)2), etc.

[0069] Optionally, the mass ratio of the lithium-philic compound precursor material to the polymer film layer is (0.1-1):1, for example 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1 or 1:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] Optionally, the reaction temperature is 60-150°C, for example 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, and the reaction time is 10-200min, for example 10min, 25min, 50min, 75min, 100min, 125min, 150min, 175min or 200min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] As another preferred technical solution in a specific embodiment, the lithium-philic compound nanoarray is modified, and the modification method includes:

[0072] The polymer film layer on which the lithium-philic compound nanoarray is grown is mixed with a lithium-philic material precursor solution, and a modification reaction is carried out to complete the modification of the lithium-philic compound nanoarray.

[0073] Optionally, the concentration of the lithium-philic material precursor solution is 10 μg / mL.

[0074] In the present invention, the total mass of the lithium-philic material and the lithium-philic compound nanoarray is 10 to 500 mg, for example, 10 mg, 50 mg, 100 mg, 150 mg, 200 mg, 250 mg, 300 mg, 350 mg, 400 mg, 450 mg or 500 mg, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0075] Furthermore, the atmosphere of the modification reaction includes an oxygen-containing atmosphere (oxygen atmosphere or air atmosphere), the temperature of the modification reaction is 80 to 120°C, for example, 80°C, 90°C, 100°C, 110°C or 120°C, etc., and the time of the modification reaction is 0.5 to 10 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0076] Those skilled in the art can adapt and adjust the specific preparation process of the modification method according to actual needs.

[0077] As another preferred technical solution in a specific embodiment, the composite method of the metal layer includes:

[0078] The metal layer is prepared on both side surfaces of the polymer film layer by using a vacuum evaporation method to obtain the composite current collector.

[0079] In the present invention, the specific vacuum evaporation process of the metal layer can be adaptively selected and adjusted by those skilled in the art according to the material and thickness of the metal material.

[0080] Optionally, the metal material in the metal layer includes but is not limited to aluminum, aluminum alloy, copper or copper alloy.

[0081] Optionally, the parameters of the vacuum evaporation may be 1-5 kW, such as 1 kW, 2 kW, 3 kW, 4 kW or 5 kW, but are not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0082] Optionally, the present invention can achieve the distribution of the metal layer in the non-nano array distribution area on the surface of the polymer film layer by regulating the content of the target material and the evaporation time during the vacuum evaporation process.

[0083] Furthermore, based on the area of ​​the non-perforated area on the surface of the polymer film layer, the content of the target material is (0.001-0.03 g) / cm 2 / min (e.g. 0.001g / cm 2 / min、0.005g / cm 2 / min、0.01g / cm 2 / min、0.015g / cm 2 / min、0.02g / cm 2 / min、0.025g / cm 2 / min or 0.03g / cm 2 / min, etc.), and the evaporation time is 5 to 30 min (for example, 5 min, 8 min, 10 min, 13 min, 15 min, 18 min, 20 min, 23 min, 25 min, 28 min or 30 min, etc.).

[0084] It should also be noted that the polymer film layer containing a through-hole structure provided by the present invention can be purchased directly, or can be prepared by itself using conventional preparation methods.

[0085] Exemplarily, the present invention provides a method for preparing a polymer film layer containing a through-hole structure:

[0086] A synthetic raw material solution of the polymer in the polymer film layer is prepared, a polymer wet film layer is obtained by a spin coating process, a polymer film layer to be punched is obtained after drying, and a laser drilling machine is used to punch holes in the polymer film layer to obtain the desired polymer film layer containing a through-hole structure.

[0087] In one embodiment, the present invention further provides a battery, comprising the composite current collector as described in one of the above embodiments or the composite current collector prepared by the preparation method described in another of the above embodiments.

[0088] The present invention does not specifically limit the specific type of battery, and is applicable to all types of batteries having a lithium deposition process, including but not limited to lithium secondary batteries, lithium primary batteries, and negative electrode-free lithium batteries.

[0089] The composite current collector provided by the present invention can be directly used as an electrode in a battery (such as a negative electrode or a positive electrode, etc.); a negative electrode active material layer can also be provided on the surface of the composite current collector; those skilled in the art can make an adaptive selection and adjustment according to actual needs.

[0090] Exemplarily, the present invention provides a negative electrode-free lithium battery structure, which includes a positive electrode, a separator, a composite current collector provided by the present invention as a negative electrode, and an electrolyte; and the preparation method of the negative electrode-free lithium battery is a conventional lithium ion battery preparation method.

[0091] like Figure 3 As shown, the present invention provides a schematic structural diagram of a composite current collector, wherein:

[0092] The composite current collector comprises:

[0093] A polymer film layer 1, wherein the polymer film layer 1 has a through-hole structure 2 penetrating through two side surfaces;

[0094] A lithium-philic compound nanoarray 3, wherein the lithium-philic compound nanoarray 3 is distributed in the non-porous areas on both sides of the polymer membrane layer 1;

[0095] and a metal layer 4 , wherein the metal layer 4 is located in the area on both sides of the polymer film layer 1 where the lithium-philic compound nanoarray 3 is not distributed.

[0096] Example 1

[0097] This embodiment provides a composite current collector, the composite current collector comprising:

[0098] A porous polyimide film, wherein the porous polyimide film has a through-hole structure penetrating through both surfaces; the pore size of the through-hole structure is 10 μm, and the hole center distance between adjacent through-holes in the same horizontal direction is 2000 μm, with the thickness direction perpendicular to the porous polyimide film as the horizontal direction;

[0099] A copper oxide nanoarray, wherein the copper oxide nanoarray is distributed in the non-porous areas on both sides of the porous polyimide film, and the copper oxide nanoarray is further modified with Au lithium-philic particles, and the array height of the copper oxide nanoarray is 5 μm;

[0100] and a copper metal layer, wherein the copper metal layer is located in the areas on both sides of the porous polyimide film where the copper oxide nanoarrays are not distributed, and the through holes of the porous polyimide film are also filled with copper metal material;

[0101] The thickness T1 of the porous polyimide film is 5 μm, and the single-side thickness T2 of the copper metal layer is 2 μm, that is, T1+T2=7 μm, T1 / (T1+T2)=5 / 7.

[0102] The preparation method of the composite current collector is as follows:

[0103] (1) Preparation of porous polyimide film

[0104] 10 mmol of 4,4-diaminodiphenyl ether (ODA) and 10 mmol of pyromellitic anhydride (PMDA) were dissolved in 40 mL of N,N-dimethylacetamide (DMAc) solvent, and stirred at room temperature for 3-4 hours under nitrogen (N2) protection to obtain a polyamic acid (PAA) solution; then a catalyst mixture prepared by mixing pyridine and propionic anhydride (pyridine is 3 wt% of PAA, and the molar ratio of propionic anhydride to PAA is 3:1) was quickly poured into the PAA solution. The film was placed in a liquid and stirred at room temperature for 5 minutes before spin coating. The film was then placed in an oven at 90°C for 30 minutes to allow the solvent to evaporate before obtaining a PAA film. The film was then heat treated at 200°C for 10 minutes and cooled to room temperature to obtain a polyimide film (the weight-average molecular weight of the polyimide was 25,000). A porous polyimide film (PPI) with a pore size of 10 μm and a spacing of 2×2 mm was prepared using an ultraviolet picosecond laser drilling machine (LASER06007). The laser wavelength used was 355 nm and the spot focus diameter was 10 μm.

[0105] (2) Preparation of composite current collector

[0106] Preparation of Au-modified copper oxide nanoarrays: PPI was cut into corresponding sizes, and the surface oil and oxide film were removed by ultrasonication in anhydrous ethanol, 1 mol / L HCl solution, and deionized water for 5 min, respectively. Then, the PPI was placed in a mixed solution of 9 mL 5 mol / L NaOH solution, 4 ml 5 mol / L CuSO4 solution, 11 mL deionized water, and 0.456 g (NH4)2S2O8 and allowed to stand for 20 min. After being taken out, it was washed three times with anhydrous ethanol and deionized water, respectively, and dried at 60 °C for 1 minute. 2h, a porous polyimide with Cu(OH)2 nanowire arrays grown on the surface was obtained; the prepared Cu(OH)2 / PPI was then placed in a prepared 10μg / mL HAuCl4 solution for 2h, taken out and washed three times with deionized water, dried and treated in an O2 atmosphere at 100°C for 2h to remove H2O in Cu(OH)2, and an Au@CuO@PPI film (copper oxide nanowire arrays, the copper oxide nanowire arrays were distributed in the non-porous areas on both sides of the porous polyimide film);

[0107] Preparation of copper layer: Place the sample in the vacuum evaporator (EB-400S, Ecopia) chamber and add a sufficient amount of target material (pure copper particles, based on the surface area of ​​the non-porous region of the porous polyimide film, the amount of target material is 0.015 g / cm 2 / min), the vacuum evaporation time is 20min, and the metal copper layer of the same thickness of 2μm is plated on both sides of the Au@CuO@PPI film to obtain the Cu-Au@CuO@PPI-Cu composite current collector.

[0108] Figure 1 The SEM image of Au@CuO@PPI in Example 1 is shown. Figure 1 It can be seen that the copper oxide nanoarray is uniform and fine, the nanoarray grows well, and the nanoarray has lithium-affinity properties. This structure can promote the uniform deposition of lithium ions on the surface of the nanoarray and enhance the cycle stability of the battery cell.

[0109] Figure 2 The SEM image of the composite current collector in Example 1 is shown. Figure 2 It can be seen that the composite current collector also includes a copper metal layer. In addition to increasing the contact points between the copper metal layers and improving the interlayer conductivity, it can also make the bonding between the copper layer and the PPI film stronger. During the copper plating process, a thin copper plating layer is formed at the edge of each hole, so that the three layers of the film are tightly buckled together, and the mutual reinforcement effect of the composite film is better exerted. At the same time, the copper plating layer can promote the stable existence of the nanoarray and prevent the nanoarray from falling off.

[0110] Example 2

[0111] This embodiment provides a composite current collector, the composite current collector comprising:

[0112] A porous polyimide film, wherein the porous polyimide film has a through-hole structure penetrating both surfaces; the pore size of the through-hole structure is 5 μm, and the hole center distance between adjacent through-holes in the same horizontal direction is 500 μm, with the thickness direction perpendicular to the porous polyimide film as the horizontal direction;

[0113] A copper oxide nanoarray, wherein the copper oxide nanoarray is distributed in the non-porous areas on both sides of the porous polyimide film, and the copper oxide nanoarray is further modified with Au lithium-philic particles, and the array height of the copper oxide nanoarray is 2 μm;

[0114] and a copper metal layer, wherein the copper metal layer is located in the areas on both sides of the porous polyimide film where the copper oxide nanoarrays are not distributed, and the through holes of the porous polyimide film are also filled with copper metal material;

[0115] The thickness T1 of the porous polyimide film is 3.5 μm, and the single-side thickness T2 of the copper metal layer is 3.5 μm, that is, T1+T2=7 μm, T1 / (T1+T2)=1 / 2.

[0116] The preparation method of the composite current collector is as follows:

[0117] (1) Preparation of porous polyimide film

[0118] 10 mmol 4,4-diaminodiphenyl ether (ODA) and 10 mmol pyromellitic anhydride (PMDA) were dissolved in 40 mL N,N-dimethylacetamide (DMAc) solvent, and stirred at room temperature for 3-4 hours under nitrogen (N2) protection to obtain a polyamic acid (PAA) solution; then a catalyst mixture prepared by mixing pyridine and propionic anhydride (pyridine is 3 wt % of PAA, and the molar ratio of propionic anhydride to PAA is 3:1) was quickly poured into the PAA solution and stirred at room temperature. After stirring for 5 minutes, spin coating was performed; then the film was placed in an oven and placed at 90°C for 30 minutes to obtain a PAA film after the solvent evaporated, and then heat treated at 200°C for 10 minutes, cooled to room temperature, and a polyimide film with a thickness of 3.5 μm was obtained (the weight-average molecular weight of polyimide was 10,000). A porous polyimide film (PPI) with a pore size of 5 μm and a spacing of 0.5×0.5 mm was prepared using an ultraviolet picosecond laser drilling machine (LASER06007). The laser wavelength used was 355 nm, and the spot focus diameter was 10 μm.

[0119] (2) Preparation of composite current collector

[0120] Preparation of Au-modified copper oxide nanoarrays: PPI was cut into corresponding sizes, and the surface oil and oxide film were removed by ultrasonication in anhydrous ethanol, 1 mol / L HCl solution, and deionized water for 5 min, respectively. Then, the PPI was placed in a mixed solution of 9 mL 5 mol / L NaOH solution, 4 ml 5 mol / L CuSO4 solution, 11 mL deionized water, and 0.456 g (NH4)2S2O8 and allowed to stand for 20 min. After being taken out, it was washed three times with anhydrous ethanol and deionized water, respectively, and dried at 60 °C for 1 minute. 2h, a porous polyimide with Cu(OH)2 nanowire arrays grown on the surface was obtained; the prepared Cu(OH)2 / PPI was then placed in a prepared 5μg / mL HAuCl4 solution for 2h, taken out and washed three times with deionized water, dried and treated in an O2 atmosphere at 120°C for 0.5h to remove H2O in Cu(OH)2, and an Au@CuO@PPI film (copper oxide nanoarrays, the copper oxide nanoarrays are distributed in the non-porous areas on both sides of the porous polyimide film);

[0121] Preparation of copper metal layer: Place the sample in the vacuum evaporator (EB-400S, Ecopia) chamber and add a sufficient amount of target material (pure copper particles, based on the surface area of ​​the non-porous region of the porous polyimide film, the amount of target material is 0.03 g / cm 2 / min), the vacuum evaporation time is 25min, and the metal copper layer of 3.5μm of the same thickness is plated on both sides of the Au@CuO@PPI film to obtain the Cu-Au@CuO@PPI-Cu composite current collector.

[0122] Example 3

[0123] This embodiment provides a composite current collector, the composite current collector comprising:

[0124] A porous polyimide film, wherein the porous polyimide film has a through-hole structure penetrating both surfaces; the pore size of the through-hole structure is 20 μm, and the hole center distance between adjacent through-holes in the same horizontal direction is 5000 μm, with the thickness direction perpendicular to the porous polyimide film as the horizontal direction;

[0125] A copper oxide nanoarray, wherein the copper oxide nanoarray is distributed in the non-porous areas on both sides of the porous polyimide film, and the copper oxide nanoarray is further modified with Au lithium-philic particles, and the array height of the copper oxide nanoarray is 3 μm;

[0126] and a copper metal layer, wherein the copper metal layer is located in the areas on both sides of the porous polyimide film where the copper oxide nanoarrays are not distributed, and the through holes of the porous polyimide film are also filled with copper metal material;

[0127] The thickness T1 of the porous polyimide film is 4 μm, and the single-side thickness T2 of the copper metal layer is 3 μm, that is, T1+T2=7 μm, T1 / (T1+T2)=4 / 7.

[0128] The preparation method of the composite current collector is as follows:

[0129] (1) Preparation of porous polyimide film

[0130] 10 mmol of 4,4-diaminodiphenyl ether (ODA) and 10 mmol of pyromellitic anhydride (PMDA) were successively dissolved in 40 mL of N,N-dimethylacetamide (DMAc) solvent, and stirred at room temperature for 3-4 hours under the protection of nitrogen (N2) to obtain a polyamic acid (PAA) solution; then a catalyst mixture prepared by mixing pyridine and propionic anhydride (pyridine is 3wt% of PAA, and the molar ratio of propionic anhydride to PAA is 3:1) was quickly poured into the PAA solution. After stirring at room temperature for 5 minutes, spin coating was performed; then the film was placed in an oven and placed at 90°C for 30 minutes to obtain a PAA film after the solvent evaporated, and then heat treated at 200°C for 10 minutes, cooled to room temperature, and a polyimide film with a thickness of 4 μm (the weight average molecular weight of polyimide was 50,000) was obtained. A porous polyimide membrane (PPI) with a pore size of 20 μm and a spacing of 5×5 mm was prepared using an ultraviolet picosecond laser drilling machine (LASER06007). The laser wavelength used was 355 nm, and the spot focus diameter was 10 μm.

[0131] (2) Preparation of composite current collector

[0132] Preparation of Au-modified copper oxide nanoarrays: PPI was cut into corresponding sizes, and the surface oil and oxide film were removed by ultrasonication in anhydrous ethanol, 1 mol / L HCl solution, and deionized water for 5 min, respectively. Then, the PPI was placed in a mixed solution of 9 mL 5 mol / L NaOH solution, 4 ml 5 mol / L CuSO4 solution, 11 mL deionized water, and 0.456 g (NH4)2S2O8 and allowed to stand for 20 min. After being taken out, it was washed three times with anhydrous ethanol and deionized water, respectively, and dried at 60 °C for 12 h, a porous polyimide with a Cu(OH)2 nanowire array grown on the surface is obtained; the prepared Cu(OH)2 / PPI is then placed in a prepared 10 μg / mL HAuCl4 solution for 2 h, taken out and washed three times with deionized water, dried and treated in an O2 atmosphere at 120°C for 0.5 h to remove H2O in Cu(OH)2, thereby obtaining an Au@CuO@PPI film (copper oxide nanowire array, the copper oxide nanowire array is distributed in the non-porous areas on both sides of the porous polyimide film);

[0133] Preparation of copper layer: Place the sample in the vacuum evaporator (EB-400S, Ecopia) chamber and add a sufficient amount of target material (pure copper particles, based on the surface area of ​​the non-porous region of the porous polyimide film, the amount of target material is 0.02 g / cm 2 / min), the vacuum evaporation time is 30min, and the metal copper layer of the same thickness of 3μm is plated on both sides of the Au@CuO@PPI film to obtain the Cu-Au@CuO@PPI-Cu composite current collector.

[0134] Example 4

[0135] The difference between this embodiment and embodiment 1 is that the aperture of the through hole structure in this embodiment is 20 μm, and the hole center distance between adjacent through holes in the same horizontal direction is 500 μm, with the thickness direction perpendicular to the porous polyimide film as the horizontal direction;

[0136] In the preparation method, step (1) uses an ultraviolet picosecond laser drilling machine (LASER06007) to prepare a porous polyimide membrane (PPI) with a pore size of 20 μm and a spacing of 0.5×0.5 mm.

[0137] The rest of the preparation methods and parameters were the same as those in Example 1.

[0138] Example 5

[0139] The difference between this embodiment and embodiment 1 is that the aperture of the through hole structure in this embodiment is 5 μm, and the hole center distance between adjacent through holes in the same horizontal direction is 5000 μm, with the thickness direction perpendicular to the porous polyimide film as the horizontal direction;

[0140] In the preparation method, step (1) uses an ultraviolet picosecond laser drilling machine (LASER06007) to prepare a porous polyimide membrane (PPI) with a pore size of 5 μm and a spacing of 5×5 mm;

[0141] In step (2), the prepared Cu(OH)2 / PPI is placed in a prepared 20 μg / mL HAuCl4 solution for 2 h.

[0142] The rest of the preparation methods and parameters were the same as those in Example 1.

[0143] Example 6

[0144] The difference between this embodiment and embodiment 1 is that the polymer in the polymer film layer in this embodiment is polyvinylidene fluoride; the lithium-philic compound nanoarray is a titanium dioxide nanoarray, and the titanium dioxide nanoarray is modified with lithium-philic material Pt nanoparticles;

[0145] In the preparation method, the polymer in the polymer film layer is polyvinylidene fluoride; the lithium-philic compound nanoarray is a titanium dioxide nanoarray, and the titanium dioxide nanoarray is modified with lithium-philic material Pt nanoparticles.

[0146] The rest of the preparation methods and parameters were the same as those in Example 1.

[0147] Example 7

[0148] The difference between this embodiment and embodiment 1 is that in this embodiment, the horizontal direction is perpendicular to the thickness direction of the porous polyimide film, and the hole center distance between adjacent through holes in the same horizontal direction is 100 μm;

[0149] In the preparation method, step (1) uses an ultraviolet picosecond laser drilling machine (LASER06007) to prepare a porous polyimide membrane (PPI) with a pore size of 10 μm and a spacing of 0.1×0.1 mm;

[0150] The rest of the preparation methods and parameters were the same as those in Example 1.

[0151] Example 8

[0152] The difference between this embodiment and embodiment 1 is that in this embodiment, the horizontal direction is perpendicular to the thickness direction of the porous polyimide film, and the hole center distance between adjacent through holes in the same horizontal direction is 5500 μm;

[0153] In the preparation method, step (1) uses an ultraviolet picosecond laser drilling machine (LASER06007) to prepare a porous polyimide membrane (PPI) with a pore size of 10 μm and a spacing of 5.5×5.5 mm;

[0154] The rest of the preparation methods and parameters were the same as those in Example 1.

[0155] Example 9

[0156] The difference between this embodiment and embodiment 1 is that the array height of the copper oxide nanoarray in this embodiment is 6 μm;

[0157] In the preparation method, the grown nanoarray was left to stand for 220 min.

[0158] The rest of the preparation methods and parameters were the same as those in Example 1.

[0159] Example 10

[0160] The difference between this embodiment and embodiment 1 is that the array height of the copper oxide nanoarray in this embodiment is 1 μm;

[0161] In the preparation method, the grown nanoarray is left to stand for 8 minutes.

[0162] The rest of the preparation methods and parameters were the same as those in Example 1.

[0163] Embodiment 11

[0164] The difference between this embodiment and embodiment 1 is that the copper oxide nanoarray of this embodiment is not modified with Au nanoparticles;

[0165] In the preparation method, the prepared Cu(OH)2 / PPI is directly treated in an O2 atmosphere at 120°C for 0.5h to remove H2O from Cu(OH)2.

[0166] The rest of the preparation methods and parameters were the same as those in Example 1.

[0167] Example 12

[0168] The difference between this embodiment and embodiment 1 is that in this embodiment, the thickness T1 of the porous polyimide film is 2 μm, the single-side thickness T2 of the copper metal layer is 7 μm, and T1 / (T1+T2)=2 / 9.

[0169] The rest of the preparation methods and parameters were the same as those in Example 1.

[0170] Embodiment 13

[0171] The difference between this embodiment and embodiment 1 is that in this embodiment, the thickness T1 of the porous polyimide film is 5 μm, and the single-side thickness T2 of the copper metal layer is 5 μm, that is, T1+T2=10 μm, T1 / (T1+T2)=1 / 2.

[0172] The rest of the preparation methods and parameters were the same as those in Example 1.

[0173] Comparative Example 1

[0174] The difference between this comparative example and Example 1 is that the polyimide film in this comparative example does not contain a pore structure;

[0175] In the preparation method, after the polyimide film is obtained, no punching treatment is performed and step (2) is directly performed.

[0176] The rest of the preparation methods and parameters were the same as those in Example 1.

[0177] Comparative Example 2

[0178] The difference between this comparative example and Example 1 is that the composite current collector of this comparative example does not have Au-modified copper oxide nanoarrays;

[0179] In the preparation method, after obtaining the porous polyimide film, the Au-modified copper oxide nanoarray is not prepared, and the PPI is directly cut into corresponding sizes. The surface oil and oxide film are removed by ultrasonic treatment in anhydrous ethanol, 1 mol / L HCl solution, and deionized water for 5 minutes, and the copper metal layer is vacuum evaporated.

[0180] The rest of the preparation methods and parameters were the same as those in Example 1.

[0181] Comparative Example 3

[0182] The difference between this comparative example and Example 1 is that the composite current collector of this comparative example does not have a copper metal layer;

[0183] In the preparation method, the Au@CuO@PPI film is prepared, that is, the composite current collector is obtained.

[0184] The rest of the preparation methods and parameters were the same as those in Example 1.

[0185] [Application and testing of composite current collectors]

[0186] a) Using the composite current collectors provided in Examples 1-13 and Comparative Examples 1-3 respectively to prepare a negative electrode-free lithium battery:

[0187] The prepared composite current collector was used as a negative electrode-free current collector, and the current collector size was (100 mm × 55 mm);

[0188] Preparation of positive electrode sheet: NCM811 is used as the positive electrode active material, carbon black is used as the conductive agent, and PVDF is used as the binder. The positive electrode active material, the conductive agent, and the binder are mixed in a mass ratio of 97:1:2, and N-methylpyrrolidone (NMP) is added to prepare the positive electrode slurry. The solid content is controlled to be 65% to 70%. 12μm aluminum foil is used as the positive electrode current collector. The positive electrode sheet is prepared by coating and drying. The size of the positive electrode sheet is 96mm×51mm.

[0189] Celgard2320 microporous polypropylene film was used as a separator; the electrolyte was 1 mol / L LiPF6 dissolved in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1.

[0190] For the full battery, the capacity ratio of the positive electrode to the negative electrode is 1. The assembly process adopts soft-pack lamination. Lamination: the positive electrode sheet, the separator, and the negative electrode current collector are stacked in order to obtain a battery cell; then assembly is performed: the stacked battery cell is hot-pressed and placed in an aluminum-plastic film, and the top and side are sealed. The electrolyte is injected into the battery, and the battery after injection is sealed. The injection coefficient is 3g / Ah. The packaged battery is subjected to formation treatment to obtain a battery to be tested.

[0191] b) The battery to be tested is subjected to an electrochemical performance test under the following test conditions: the charge and discharge cut-off voltage is 2.8-4.2V, the charge and discharge current is 1A / g, and the test is terminated after 200 cycles.

[0192] c) Extreme hot box temperature test: After the battery cell is placed at 70℃ for 30 minutes to reach thermal equilibrium, the temperature is raised to 75℃ at a rate of 5℃ / min and kept at that temperature for 30 minutes. The battery cell voltage is recorded, and this process is repeated until the battery cell failure voltage reaches zero. The maximum temperature that the battery cell can withstand is recorded.

[0193] The test results are shown in Table 1.

[0194] Table 1

[0195]

[0196] From Table 1, we can get:

[0197] By using a composite current collector, with the help of lithium-philic materials and nanoarrays, better first efficiency and capacity retention can be obtained, indicating that the presence of the nanoarray enhances electronic conductivity and increases energy conversion efficiency. The improvement in cycle stability depends on the injection of lithium-philic materials. The data from the extreme hot box show that the use of a composite current collector plus lithium-philic materials can obtain better structural stability. Uniform lithium ion deposition and a tight SEI film can improve the thermal stability of the battery cell.

[0198] In summary, the composite current collector provided by the present invention, the polymer film layer, the lithium-philic compound nanoarray and the metal layer cooperate in structure and distribution, have excellent mechanical flexibility, are not prone to break, and even if they break, they cannot reach the standard of piercing the diaphragm, thereby better avoiding the risk caused by breakage and improving the thermal stability of the battery; the through-hole structure of the polymer film layer realizes electronic conduction on both sides, reduces the density of the composite current collector, and improves the energy density of the battery; the lithium-philic compound nanoarray has excellent lithium-philic properties, which will cause lithium metal to be deposited along the surface of the nanoarray, and at the same time, the three-dimensional structure formed by the array constructed between the nanofibers can be deposited for lithium ions. It provides a very rich deposition space, effectively slows down the volume change of the negative electrode during the cycle, and effectively regulates the directional deposition of lithium metal. The nanoarray as a carrier framework of lithium metal can not only reduce the local current density, but also limit the volume expansion of the negative electrode and the growth of lithium dendrites during the charge and discharge process, and also increase the contact points of the metal layer; the specific distribution of the metal layer plays a role in improving the conductivity of the current collector, and fills the area on the surface of the polymer film layer where the nanoarray is not distributed, making up for the distribution gap of the nanoarray, and having a stronger bonding force with the polymer film, better playing the role of mutual reinforcement of the composite film, and at the same time can also promote the stable existence of the nanoarray and prevent the nanoarray from falling off.

[0199] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite current collector, characterized in that: The composite current collector comprises: A polymer film layer, wherein the polymer film layer has a through-hole structure penetrating through two side surfaces; A lithium-philic compound nanoarray, wherein the lithium-philic compound nanoarray is distributed in the non-porous areas on both sides of the polymer membrane layer; and a metal layer, wherein the metal layer is located in the area where the lithium-philic compound nanoarray is not distributed on the two side surfaces of the polymer film layer.

2. The composite current collector according to claim 1, characterized in that: The polymer in the polymer film layer satisfies at least one of the following conditions (a) to (b): (a) the polymer in the polymer film layer includes at least one of polyimide, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate, polyethylene oxide or polyvinyl alcohol; (b) The weight average molecular weight of the polymer in the polymer film layer is 10,000 to 50,000.

3. The composite current collector according to claim 1, characterized in that: The lithium-philic compound nanoarray satisfies at least one of the following conditions (c) to (e): (c) the lithium-philic compound nanoarray comprises at least one of a copper oxide nanoarray, a titanium dioxide nanoarray or a nickel hydroxide nanoarray; (d) the array height of the lithium-philic compound nanoarray is 2 to 5 μm; (e) The lithium-philic compound nanoarray further includes a modifier, wherein the modifier includes a lithium-philic material, and the lithium-philic material includes at least one of Au, Pt or Ag.

4. The composite current collector according to claim 1, characterized in that: The through holes in the polymer film layer satisfy at least one of the following conditions (f) to (g): (f) The pore size of the through-hole structure is 5 to 20 μm; (g) With the thickness direction perpendicular to the polymer film layer as the horizontal direction, the hole center distance between adjacent through holes in the same horizontal direction is 500 to 5000 μm.

5. The composite current collector according to claim 1, characterized in that: The thickness T1 of the polymer film layer and the thickness T2 of the metal layer satisfy the following conditions: 2 μm ≤ T1 + T2 ≤ 9 μm, and / or 1 / 2 ≤ T1 / (T1 + T2) ≤ 5 / 7.

6. The composite current collector according to claim 1, characterized in that: The metal in the metal layer is also filled in the through hole.

7. A method for preparing a composite current collector according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: The lithium-philic compound nanoarrays are grown on both sides of the polymer film layer containing the through-hole structure, and then the metal layers on both sides of the polymer surface are composited to obtain the composite current collector.

8. The preparation method according to claim 7, characterized in that: The growth method of the lithium-philic compound nanoarray comprises: The polymer film layer, chemical etching solution and lithium-philic compound precursor material are mixed and reacted to obtain a lithium-philic compound nanoarray.

9. The preparation method according to claim 7 or 8, characterized in that: The lithium-philic compound nanoarray is modified, and the modification method includes: The polymer film layer on which the lithium-philic compound nanoarray is grown is mixed with a lithium-philic material precursor solution, and a modification reaction is carried out to complete the modification of the lithium-philic compound nanoarray.

10. The preparation method according to claim 7, characterized in that: The composite method of the metal layer comprises: The metal layer is prepared on both side surfaces of the polymer film layer by using a vacuum evaporation method to obtain the composite current collector.

11. A battery, characterized in that: The battery comprises the composite current collector according to any one of claims 1 to 6 or the composite current collector prepared by the preparation method according to any one of claims 7 to 10.

Citation Information

Patent Citations

  • Preparation method and application of surface modified carbon cloth 3D skeleton

    CN115000412A

  • Ultrathin current collector prepared by adopting double-pulse ion beam technology and method and device thereof

    CN117026165A

  • Current collector for electrochemical cells circulating lithium ions

    CN117059815A

  • Composite current collector with electrical interconnection and through-hole structure, preparation method thereof, battery pole pieces and lithium ion battery

    CN109698359A

  • Composite current collector, preparation method thereof and lithium battery pole piece

    CN111883777A